Polydorid polychaeta as pests in cultivated oysters : a case study of polydorid infestation on a South African oyster farm, including a literature review and proposed best management practices for the reduction of polychaete infestation in the culture of molluscs - Brink, Jacobus Abraham (Stellenbosch : Stellenbosch University, 2012)
Assignment (MPhil)--University of Stellenbosch, 2006.